Analysis of Corporate Culture Existence in Pertamina EP - Darmadi, Linda Pratiwi; Gustomo, Aurik (Journal of Business and Management, 2012)
The research aimed to know the current condition of corporate culture in Pertamina Eksplorasi Produksi (PEP), its culture design and Management approach related to employees implementation of corporate culture. The methodology used is by collected PEP Company’s profile, business ethics and works (EKB) files and list of employees’ population. Primary data is collected by questionnaires that distributed to 130 samples and interview with management. There were 3 dimensions (sincere, strong and sensible) which created 19 variables based on business work and ethics files of PEP. Those variables created 4 new factors (professionalism, commercial branding, corporate confidentiality and courage).  Overall, the most understood by employees is factor commercial branding and the lowest is corporate’s confidentiality. Suggestion PEP is management should create atmosphere of less underestimated the small problem that rise in workforce, for example, in confidentiality of data, employees still underestimated few problem like destroy the data that period of retention already expired.Keywords; Corporate Culture, Pertamina EP, Factor Analysis, Business Ethics and Works.Category: Human Resources Management; Organizational Development and Culture.